Long-Term Behavior Related to Water Ingress in Mortars Which Combine Expanded and Natural Cork Lightweight Aggregates and Eco-Friendly Cements - José Marcos Ortega; Fernando G. Branco; Luís Pereira (Buildings, 2023)
The water ingress plays an important role in building materials’ degradation. The use of lightweight aggregates is interesting in terms of sustainability, because they reduce the density of cement-based materials, among other advantages. The development and use of new lightweight aggregates, such as cork granulates, is a current research topic. In the present work, water ingress performance of sustainable mortars which combined expanded and natural cork aggregates and cements with slag, fly ash and limestone has been studied. Mortars produced with sand and expanded clay were also prepared. Bulk density, water absorption, drying capacity and gel and capillary pores were studied. Tests were carried out at 28 days and 1 year. A good behavior has been generally observed when an addition was incorporated to the binder, especially slag or fly ash. Regarding the new non-standardized lightweight cork aggregates, mortars with natural cork showed lower water absorption and lower volume of permeable pore space in the long term than mortars with expanded cork. At one year, natural cork mortars had an adequate water absorption performance compared to those with expanded clay, which may be due to the high volume of small capillary pores (100 nm–1 µm) in natural cork mortars.